2017
DOI: 10.1161/jaha.116.005198
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐1 Preserves Blood‐Brain Barrier Integrity Through Deleted in Colorectal Cancer/Focal Adhesion Kinase/RhoA Signaling Pathway Following Subarachnoid Hemorrhage in Rats

Abstract: BackgroundNetrin‐1 (NTN‐1) has been established to be a novel intrinsic regulator of blood‐brain barrier (BBB) maintenance. This study was carried out to investigate the potential roles of exogenous NTN‐1 in preserving BBB integrity after experimental subarachnoid hemorrhage (SAH) as well as the underlying mechanisms of its protective effects.Methods and ResultsA total of 309 male Sprague‐Dawley rats were subjected to an endovascular perforation model of SAH. Recombinant NTN‐1 was administered intravenously 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…In our study, we found that the Mas expression in left hemisphere of brain was decreased and reached to the lowest level at 24 h after SAH. According to previous studies [47] , [48] , [49] , the EBI was much worse at 24 h when compared with other time points after experimental SAH, of which the damaging factors may include neuronal apoptosis, brain edema, and inflammation. As Mas is primarily produced in neurons, the expression of Mas was the lowest at 24 h after SAH, corresponding to the severity of EBI.…”
Section: Discussionmentioning
confidence: 63%
“…In our study, we found that the Mas expression in left hemisphere of brain was decreased and reached to the lowest level at 24 h after SAH. According to previous studies [47] , [48] , [49] , the EBI was much worse at 24 h when compared with other time points after experimental SAH, of which the damaging factors may include neuronal apoptosis, brain edema, and inflammation. As Mas is primarily produced in neurons, the expression of Mas was the lowest at 24 h after SAH, corresponding to the severity of EBI.…”
Section: Discussionmentioning
confidence: 63%
“…Netrin-1 (R&D Systems, 6419-N1-025) was given at 45 µg/kg in phosphate-buffered saline (PBS), and administered through tail vain with a total volume of 200 µL at 1 hour after surgery, while the equal volume of PBS was given in control group and surgery group. The dose of netrin-1 was based on the researches using other models of acute in ammation with slight modi cation [21]. 3 POD mouse model A simple laparotomy was performed under iso urane anesthesia using the methods described in our previous studies [22].…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Overexpression of NTN-1 promoted angiogenesis and improved long-term neurological functions following ischemic stroke. Recent studies indicated that NTN-1 preserved BBB integrity in model of traumatic brain injury and experimental autoimmune encephalomyelitis [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Perivascular astrocytes have been found to engage in promoting brain neovascularization, vessel differentiation, and stabilization [ 52 , 54 ], suggesting that angiogenesis induced by netrin-1 may be mediated partly through the DCC-expressing perivascular astrocytes. Moreover, as perivascular astrocytes have a supportive role in the maintenance of the brain–blood barrier [ 55 ], and netrin-1 has been found to support blood–brain barrier integrity and protect the central nervous system against injury [ 56 , 57 ], we speculate that netrin-1 and DCC may also play a positive role in the restoration of the brain–blood barrier after cerebral ischemia, which also needs further clarification.…”
Section: Discussionmentioning
confidence: 99%